PERBANDINGAN ONLINE SHOP DAN PASAR OFFLINE DALAM PERSPEKTIF ISLAM - Saputra, Rio Febrian Saven; Muarif, Dzikrian; Romadhan, M. Iqbal; Gusnanda, Khoiri (STAI Darul Qalam Tangerang, 2024)
The purpose of this study is to find out the comparison of marketing strategies with online and offline systems as well as to find out marketing strategies with online and offline systems in the Islamic economic review. Researchers use a qualitative approach with secondary data collection techniques obtained from various sources, namely, previous journals, websites, online books and others. From the results of the study, it can be concluded that offline marketing strategies and online marketing strategies are permissible in an Islamic economic perspective as long as they are based on the principle of consensual or voluntary from both parties, namely from sellers and buyers and there is no fraud or fraud, so that each party gets what should be received in full, not reduced rights and harmed or dzolim